Validation and reliability testing of Reflective Functioning Questionnaire (RFQ) Indonesian Version - Mahaputra, Mahaputra; Sylvia Detri Elvira; Petrin Redayani Lukman; Martina Wiwiek Nasrun; Tjhin Wiguna (Faculty of Medicine, Universitas Airlangga, 2025)
Introduction: Reflective function refers to the capacity to comprehend emotions, beliefs, and behaviors in oneself and others. Mental disorders are frequently associated with deficits in mentalizing capabilities. These deficits compromise an individual’s capacity for self-reflection and understanding of mental states, impeding one’s ability to regulate both mental states and interpersonal relationships. The Reflective Functioning Questionnaire (RFQ) is a practical tool to measure reflective function, but it has not yet been adapted into Indonesian, a crucial step toward addressing the needs of local populations. This study aimed to develop an Indonesian version of the RFQ with robust validity and reliability. Methods: The English RFQ was translated into Indonesian using standard guidelines, including forward and backward translation by certified translators. Content and face validity were assessed through expert panel reviews to ensure cultural and linguistic relevance. Construct validity was evaluated using confirmatory factor analysis (CFA), and reliability testing was conducted using Cronbach’s Alpha. A pilot study with 10 subjects was conducted to refine the instrument, followed by testing with a sample of 100 participants. Results: The final Indonesian RFQ consists of 11 items across two subscales: RFQu and RFQc. CFA indicated a good model fit (χ² = 1.16, p = 0.55, and RMSEA = 0.041). Reliability testing showed strong internal consistency, with Cronbach’s Alpha values of 0.89 for RFQc and 0.87 for RFQu. Conclusion: The modified Indonesian RFQ demonstrated excellent validity and reliability, providing a robust tool for assessing reflective function in clinical and research settings.